PENGARUH PENILAIAN KINERJA DAN KOMPENSASI TERHADAP MOTIVASI KERJA PT PERTAMINA TRANS KONTINENTAL - Fatimah Azzahra; Sugeng Prayetno (Bajang Institute, 2024)
This study aims to determine and explain the effect of performance appraisal and compensation on the work motivation of PT Pertamina Trans Kontinental. This type of research is explanatory research with a quantitative approach. The population in this study were employees of PT Pertamina Trans Kontinental, the sample used in this study was 50 employees. The sample was obtained from calculations using the Slovin formula. Data was obtained directly from respondents with a direct research instrument in the form of a questionnaire. The data analysis used is descriptive statistical data analysis and multiple linear regression analysis processed using SPSS version 25. The results showed that there was a positive and significant influence between performance appraisal and compensation on employee motivation both partially and simultaneously at PT Pertamina Trans Kontinental. The total R-Square result was calculated to be 0.946, representing 94.6%. This indicates that the level of effect of performance appraisal on work motivation accounts for 94.6% simultaneously, while the remaining 5.4% is due to extraneous variables not included in the study